Heart Failure and Frailty in the Community-Living Elderly Population: What the UFO Study Will Tell Us - Fung, Erik; Hui, Elsie; Yang, Xiaobo; Lui, Leong T.; Cheng, King F.; Li, Qi; Fan, Yiting; Sahota, Daljit S.; Ma, Bosco H. M.; Lee, Jenny S. W.; Lee, Alex P. W.; Woo, Jean (Frontiers in Physiology, 2018)
Heart failure and frailty are clinical syndromes that present with overlapping phenotypic characteristics. Importantly, their co-presence is associated with increased mortality and morbidity. While mechanical and electrical device therapies for heart failure are vital for select patients with advanced stage disease, the majority of patients and especially those with undiagnosed heart failure would benefit from early disease detection and prompt initiation of guideline-directed medical therapies. In this article, we review the problematic interactions between heart failure and frailty, introduce a focused cardiac screening program for community-living elderly initiated by a mobile communication device app leading to the Undiagnosed heart Failure in frail Older individuals (UFO) study, and discuss how the knowledge of pre-frailty and frailty status could be exploited for the detection of previously undiagnosed heart failure or advanced cardiac disease. The widespread use of mobile devices coupled with increasing availability of novel, effective medical and minimally invasive therapies have incentivized new approaches to heart failure case finding and disease management.